Paris vs. Murchison: Impact of hydrothermal alteration on organic matter in CM chondrites. (1st September 2017) - Vinogradoff, V.; Le Guillou, C.; Bernard, S.; Binet, L.; Cartigny, P.; Brearley, A.J.; Remusat, L.
Abstract: Unravelling the origin of organic compounds that were accreted into asteroids requires better constraining the impact of asteroidal hydrothermal alteration on their isotopic signatures, molecular structures, and spatial distribution. Here, we conducted a multi-scale/multi-technique comparative study of the organic matter (OM) from two CM chondrites (that originate from the same parent body or from identical parent bodies that accreted the same mixture of precursors) and underwent a different degree of hydrothermal alteration: Paris (a weakly altered CM chondrite – CM 2.8) and Murchison (a more altered one – CM 2.5). The Paris insoluble organic matter (IOM) shows a higher aliphatic/aromatic carbon ratio, a higher radical abundance and a lower oxygen content than the Murchison IOM. Analysis of the OM in situ shows that two texturally distinct populations of organic compounds are present within the Paris matrix: sub-micrometric individual OM particles and diffuse OM finely distributed within phyllosilicates and amorphous silicates. These results indicate that hydrothermal alteration on the CM parent body induced aromatization and oxidation of the IOM, as well as a decrease in radical and nitrogen contents. Some of these observations were also reported by studies of variably altered fragment of Tagish Lake (C2), although the hydrothermal alteration of the OM in Tagish Lake was apparently much more severe. Finally, comparison with data available in the literature suggests that the parent bodies of other chondrite petrologic groups could have accreted a mixture of organic precursors different from that accreted by the parent body of CMs.